Trends in HIV infection surveillance data among men who have sex with men in Norway, 1995-2011 - Jakopanec Irena; Grjibovski Andrej M; Nilsen Øivind; Blystad Hans; Aavitsland Preben (BMC, 2013)
Abstract Background Recent reports on the growing HIV epidemic among men who have sex with men (MSM) in the EU/EEA area were accompanied by an increase of reported HIV among MSM in Oslo, Norway in 2003. Our study with data from 1995 to 2011 has described the recent trends of HIV among MSM in Norway and their socio-demographic and epidemiological characteristics. Methods The data were collected from the Norwegian Surveillance System for Communicable Diseases. Cases were described by age, place of infection, clinical presentation of HIV infection, STI co-infection and source partner. We used simple linear regression to estimate trends over time. Results During the study period, 991 MSM, aged from 16 to 80 years, were newly diagnosed with HIV. No significant trends over time in overall median age (36 years) were observed. Most of the MSM (505, 51%) were infected in Oslo. In the years 1995-2002, 30 to 45 MSM were diagnosed with HIV each year, while in the years 2003-2011 this increased to between 56 and 97 cases. The proportion of MSM, presenting with either AIDS or HIV illness, decreased over time, while asymptomatic and acute HIV illness increased (p for trend=0.034 or less). STI co-infection was reported in 133 (13%) cases. An overall increase of syphilis co-infected cases was observed (p for trend <0.001). A casual partner was a source of infection in 590 cases (60%). Conclusions Though the increases described could be attributed to earlier testing and diagnosis, no change in the median age of cases was observed. This indicates that it is likely that there has been an increase in HIV infections among MSM in Norway since 2003. The simultaneous increase in STI co-infections indicates risky sexual behaviour and a potential to spread both HIV and other sexually transmitted infections.